2020
DOI: 10.3390/antiox9111032
|View full text |Cite
|
Sign up to set email alerts
|

Muscle Antioxidant Activity and Meat Quality Are Altered by Supplementation of Astaxanthin in Broilers Exposed to High Temperature

Abstract: This study investigated the effect of dietary astaxanthin (AST) on the meat quality, antioxidant status, and immune response of chickens exposed to heat stress. Four hundred and eighty male broilers were assigned to four treatments including AST0, AST20, AST40, and AST80 with 0, 20, 40, and 80 ppm astaxanthin supplementation levels, respectively. There was a linear decrease of malondialdehyde (MDA) in leg muscle. Catalase and superoxide dismutase levels in the plasma were linearly increased. There was a linear… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
46
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 44 publications
(49 citation statements)
references
References 46 publications
3
46
0
Order By: Relevance
“…Under certain conditions, such as heat stress, gut bacteria produce more ROS and RNS, which results in oxidative stress. As for the broilers, the selective breeding of fast-growing birds has increased their susceptibility to heat stress, that may disrupt the immune system and cardiac functions, thus increasing oxidative reactions that compromise meat quality ( Hosseindoust et al., 2020 ). Interindividual variation in response to stress or other environmental stimuli might be different and therefore contribute to the different gut microbioal compostion.…”
Section: Discussionmentioning
confidence: 99%
“…Under certain conditions, such as heat stress, gut bacteria produce more ROS and RNS, which results in oxidative stress. As for the broilers, the selective breeding of fast-growing birds has increased their susceptibility to heat stress, that may disrupt the immune system and cardiac functions, thus increasing oxidative reactions that compromise meat quality ( Hosseindoust et al., 2020 ). Interindividual variation in response to stress or other environmental stimuli might be different and therefore contribute to the different gut microbioal compostion.…”
Section: Discussionmentioning
confidence: 99%
“…It has been shown that upregulated HSP70/90 prevents heat-stress-induced intestinal mucosa damage by enhancing antioxidant status [ 43 , 167 ]. Hosseindoust et al [ 168 ] reported that the level of HSP70 was significantly upregulated in different sections of the small intestine of chicken under acute heat stress. However, the expression of HSP family members in intestinal segments differs between genotypes under heat-stress conditions [ 39 ].…”
Section: Cytoprotective Role Of Hsps Against Heat-stress-induced Imentioning
confidence: 99%
“…As the traditional broiler’s meat is costly because of higher meat quality compared with modern broilers, the low meat quality can compromise the marketability. Moreover, the high stress level affects polyunsaturated fatty acids of meat, which increases the vulnerability to oxidative deterioration [ 3 , 4 , 5 ]. The control of lipid oxidation associated with SD entails the supplementation of antioxidant factors to block the production of free radicals [ 6 ].…”
Section: Introductionmentioning
confidence: 99%